2011
DOI: 10.1149/1.3559458
|View full text |Cite
|
Sign up to set email alerts
|

Deposition Temperature and Thermal Annealing Effects on the Electrical Characteristics of Atomic Layer Deposited Al2O3 Films on Silicon

Abstract: Atomic layer deposition (ALD) of Al2O3 is of interest for a wide range of micronanoelectronic applications, where the electrical properties of the deposited layers can be strongly affected by deposition conditions and post-deposition treatments. In this work, a mercury-probe capacitance-voltage characterization is carried out on Al2O3 films deposited on silicon by ALD at different temperatures and subjected to various thermal treatments in N2 ambient. Effective positive charges located at the semiconductor/die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 32 publications
7
22
0
Order By: Relevance
“…The Q F of as-deposited films is positive which are listed in Table III. Rafi et al 36 also observed positive fixed charges in the Al 2 O 3 films deposited at 100 Table III) which confirms that there is an activation of negative fixed charges in these films. The density and polarity of fixed charges are related to the deposition process of oxide films and is associated with local non-stoichiometry or structural defects.…”
Section: Capacitance-voltage (C-v) Measurementsmentioning
confidence: 54%
See 1 more Smart Citation
“…The Q F of as-deposited films is positive which are listed in Table III. Rafi et al 36 also observed positive fixed charges in the Al 2 O 3 films deposited at 100 Table III) which confirms that there is an activation of negative fixed charges in these films. The density and polarity of fixed charges are related to the deposition process of oxide films and is associated with local non-stoichiometry or structural defects.…”
Section: Capacitance-voltage (C-v) Measurementsmentioning
confidence: 54%
“…All these results demonstrate that deposition temperature and post-deposition annealing both play important role for surface passivation. [33][34][35][36][37][38] ) as a function of t anl of as-deposited and annealed (t anl = 90 s, 105 s, 120 s) samples of S 100 , S 200 and S 300 . The minimum SRV value (∼7 cm/s) obtained using low thermal budget RTP process is quite comparable to the values realized with high thermal budget.…”
Section: Minority Carrier Lifetimementioning
confidence: 99%
“…To our knowledge it was the first time that the role of the SiO 2 interlayer on the built-in charge density was clearly established even though it has been often speculated that the presence of negative charges in Al 2 O 3 thin films on silicon is associated with the presence of interfacial SiO 2 between the silicon and the Al 2 O 3 . [10][11][12][13] In our previous work we did, however, not conclusively establish the origin and physical location of the charges in the stacks. Furthermore, the SiO 2 interlayers (1-13 nm) were prepared solely by atomic layer deposition (ALD) and only n-type silicon wafers were used.…”
Section: Introductionmentioning
confidence: 76%
“…26,30 The model assumes a 20 nm passivation layer with an index of refraction of 1.63. 31 To minimize noise in the data, 50 measurements are averaged for high lifetime (>100 ls) samples. Error bounds for lifetime are 610%.…”
Section: à2mentioning
confidence: 99%